Epistemology of ceremonial and protocol: Theoretical approach to qualitative research - Pulido-Polo, Marta; Parrilla Amador, Margarita (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The current academic context shows an important deficit of scientific texts related to the study of the ceremonial and the protocol in high-impact indexed academic journals. The relational perspective of the organization of events allows us to approach these disciplines from the methodological solidity that the social sciences allow. Thus, the main objective of this work is to make an approach to the epistemological question, framed in the Social Sciences, which allows the development of excellent methodological designs, of a qualitative nature, for the scientific study of the ceremonial and the protocol.